Long working hours, sedentary work, noise, night shifts and risk of ischaemic heart disease. Issue 5 (8th August 2022) - Eng, Amanda; Denison, Hayley J; Corbin, Marine; Barnes, Lucy; 't Mannetje, Andrea; McLean, Dave; Jackson, Rod; Laird, Ian; Douwes, Jeroen
Abstract : Objective: Ischaemic heart disease (IHD) is a leading cause of death in Western countries. The aim of this study was to examine the associations between occupational exposure to loud noise, long working hours, shift work, and sedentary work and IHD. Methods: This data linkage study included all New Zealanders employed and aged 20–64 years at the time of the 2013 census, followed up for incident IHD between 2013 and 2018 based on hospitalisation, prescription and death records. Occupation and number of working hours were obtained from the census, and exposure to sedentary work, loud noise and night shift work was assessed using New Zealand job exposure matrices. HRs were calculated for males and females using Cox regression adjusted for age, socioeconomic status, smoking and ethnicity. Results: From the 8 11 470 males and 7 83 207 females employed at the time of the census, 15 012 male (1.9%) and 5595 female IHD cases (0.7%) were identified. For males, there was a modestly higher risk of IHD for the highest category (>90 dBA) of noise exposure (HR 1.19; 95% CI 1.07 to 1.33), while for females exposure prevalence was too low to calculate an HR. Night shift work was associated with IHD for males (HR 1.10; 95% CI 1.05 to 1.14) and females (HR 1.25; 95% CI 1.17 to 1.34). The population attributable fractions for night shift work were 1.8% and 4.6%, respectively. No clear associations with working long hours and sedentary work were observed. Conclusions: This study suggests that occupational exposures to high levels of noise and night shift work might be associated with IHD risk.